Advance Directive Completion Among Older American Couples: A Dyadic Perspective on the Role of Cognitive Function and Other Factors. (10th June 2021) - Lu, Peiyi; Kong, Dexia; Lee, Jeongeun; Shelley, Mack
Abstract: Objective: Dyadic perspective is scarce in existing advance directive (AD) literature. Particularly, the significance of one's own and/or one's partner's cognitive function on AD remains unknown. This study investigates the relationship of cognitive function and other factors with AD completion within the spousal context. Method: Data from the Health and Retirement Study (2014–2015) were used. Older heterosexual couples (age ≥65) married for 10+ years were asked if they had a living will and/or appointed a durable power of attorney for health care (DPAHC). Structural equation models examined the actor and partner effects of sociodemographic, health, and couple-level characteristics on wife's and husband's AD, respectively. Results: Moderate spousal interdependence was observed in living will (kappa coefficient, κ = .60) and DPAHC (κ = .53). Older age and higher education were related to both spouses having AD. Less household wealth and being racial/ethnic minority were associated with a lower probability of having AD. Notable gender contrasts in actor and partner effects were found. Wife's higher level of cognitive function was associated with husband's AD completion. Contrarily, husband's lower level of cognitive function was associated with wife's AD completion. Retirement status had primarily actor effects for both husbands and wives. More chronic conditions were linked to husband's AD completion. Discussion: The spousal interdependence of AD warrants practitioner efforts to facilitate family-oriented end-of-life planning. Wives and husbands may have different thoughts regarding their spouse's cognitive capacity to surrogate. Facilitating couple-based discussions may be a feasible approach to promote engagement with AD among older adults.